ANALISIS HUBUNGAN KEKERABATAN MACANG (Mangifera foetida Lour.) DI SUMATERA BAGIAN TENGAH - Anto '; Fitmawati '; N. Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The diversity of Mangifera foetida Lour. (macang) in central Sumatra has not beenexplored and inventoried. On the other hand, the diversity of cultivars and varieties ofthis species is endangered due to the lost of its natural habitat. This research aimed toanalyze the diversity of macang in central Sumatra. The research was carried out fromDecember 2011 to June 2013. The morphological and agronomical characters of a totalof 66 macang trees had been observed. All of these observed characters were then scoredand analyzed using NTSYSpc 2.02 to determine their clustering and using Minitab toanalyze the principle component and correlation of Pearson. The result showed that thesimilarity coefficient ranged from 0.17 to 0.76. Dendogram constructed from thesimilairty coefficient showed two main groups, that clustered not based on the samplelocations but based on the character similarity (fruit color). The first group consisted of65 individuals and second group consisted of one individual. The result of Principlecomponent analysis showed two main groups, with the diversity accumulation value was40%. The results of correlation analysis of 66 characters showed that six characterswere positively corellated.